Relative effects of inhaled corticosteroids on immunopathology and physiology in asthma: a controlled study. Issue 10 (October 1996) - Burke, C. M.; Sreenan, S.; Pathmakanthan, S.; Patterson, J.; Schmekel, B.; Poulter, L. W.
Abstract : BACKGROUND: Although corticosteroids are recognised as the most efficacious treatment for bronchial asthma, their mode of action remains unclear. A placebo controlled trial was undertaken of the effect of inhaled corticosteroids on physiological and immmunopathological parameters in asthmatic patients in whom the correlations between these indices were tested after treatment. METHODS: Sixteen patients (two women) with asthma entered a double blind, placebo controlled, parallel study during which they inhaled either budesonide 800 micrograms twice daily or matching placebo for six weeks. Spirometric parameters and bronchial reactivity to histamine and terbutaline were measured and endobronchial biopsy samples were taken before and after treatment. Patients recorded morning and evening flow rates during the treatment period. The biopsy samples were subjected to immunohistological analysis to determine the disposition of inflammatory cells within the bronchial wall. RESULTS: Treatment with budesonide resulted in a significant improvement in the 25-75% forced expiratory flow (FEF25-75) from a mean of 133 l/min before treatment to 169 l/min after treatment, and in the morning peak expiratory flow rate (PEFR) from a mean of 384 l/min before treatment to 415 l/min after treatment. No changes were seen in the placebo group. Comparison between the changes in the immunopathological indices after six weeks of treatment with placebo or budesonide showed a significant reduction in the numbers of mast cells (0.5/unit area to 0.2/ unit area), activated eosinophils, and the expression of HLA-DR antigens (relative density -1.9 before to 1.02 after treatment) on inflammatory cells in response to treatment with budesonide. Although reductions in the numbers of other inflammatory cells within the bronchial wall were recorded using immunohistological analysis, these changes were not statistically significant. Significant correlations were found between changing immunological indices and lung physiology. CONCLUSIONS: This controlled study shows that inhaled corticosteroids cause improvement in physiological and immunopathological parameters in patients with stable asthma that are not seen with placebo, and that cause and effect relationships may exist between these two measures of disease status.